ANALYTICAL THINKING PROCESS OF STUDENTS IN SOLVING MATHEMATICAL PROBLEMS OF QUADRATIC FUNCTIONS - Naela Nur Azizah; Susiswo Susiswo; Sisworo Sisworo (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Analytical thinking is an ability to observe objects thoroughly and solve facts comprehensively. This study is set to describe students' analytical thinking processes in solving mathematical problems, especially in quadratic functions. It employs a qualitative approach with qualitative descriptive research. The subjects in this study are one student with high mathematics ability, one student with medium mathematics ability, and one student with low mathematics ability of Tenth Grade of State Islamic Senior High School 3 Tulungagung. Data collection are carried out through task-based interviews. Meanwhile, data analysis technique are data reduction, data presentation, and conclusion Based on the results of data analysis and discussion, it is concluded that (1) The student with high mathematical ability pass several stages, namely differentiating, and organizing, he/he can solve the quadratic function problem properly according to the problem solving steps. (2) The student with medium mathematical ability can go through differentiating and organizing stages. But at the attributing stage, he/she are less able to solve problems based on the objectives. (3) The student with low mathematical ability tends not to pass differentiating, organizing, and attributing analytical thinking stages. He/she are less able to solve quadratic function problems according to the solving steps.Keywords: Analytical thinking process; problem solving; quadratic functions